If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(2x-1)=2x^2(2)+5x-12
We move all terms to the left:
(2x-1)-(2x^2(2)+5x-12)=0
We do not support expression: x^22
| (2x+6)(2x-10)=0 | | (4x+1)²=(x+1)²+(3x+6)² | | 25=8n-6 | | 15x+5+-1+27x=130 | | 9y+21=89×= | | 6.2n=55.8 | | -4x2+3=-9 | | (6+x)×7=63 | | -4x8=52 | | -8=-7c | | 3m-15=-7.M=3 | | 5+2x-8+6x=-11. | | x÷7=-77 | | 2(3x-1)=3(2x-1) | | 43(x-7)=180 | | 8+40÷4×5−3=x | | 36.3=a-10.45 | | 13x-111=7x-57 | | 5-2(x+3)=-15. | | x/9-11=-7 | | 5=5x+-7 | | y+10y-24=0 | | 30v+36-6v-5=1 | | 24=f+4 | | 3^3x=243 | | 7-6=g | | w−12.1=7.53 | | 17=u+14 | | 2(x-3)+4x=18. | | 6a-2+3=-2 | | 20/300=x/40 | | 26=j+14 |